Molecular genetic aspects of sudden cardiac death: a literature review - A. A. Ivanova; V. N. Maksimov (Бюллетень сибирской медицины, 2018)
Sudden cardiac death (SCD) continues to be a relevant and significant problem in modern medicine. Modern trends in medicine are associated with the widespread introduction of personalized, preventive strategies aimed at correcting risk factors for pathology, identifying predispositions to it and conducting prevention before the development of clinical symptoms. Nowadays, a huge number of studies of the molecular genetic basis of SCD are conducted. Studies of case-control design using routine methods of molecular genetic research continue to be popular. Research using modern, highly effective methods (sequencing of the next generation (NGS), full-genome associative studies (GWAS)) have become more frequent. The molecular genetic markers of SCD found in such studies can be used effectively to diagnose a predisposition to SCD and prevent its development in persons with known and unknown cardiac pathology.